2023
DOI: 10.3390/molecules29010233
|View full text |Cite
|
Sign up to set email alerts
|

Pleiotropic Potential of Evernia prunastri Extracts and Their Main Compounds Evernic Acid and Atranorin: In Vitro and In Silico Studies

Elżbieta Studzińska-Sroka,
Magdalena Bulicz,
Marika Henkel
et al.

Abstract: Evernia prunastri is a lichen widely distributed in the Northern Hemisphere. Its biological properties still need to be discovered. Therefore, our paper focuses on studies of E. prunastri extracts, including its main metabolites evernic acid (EA) or atranorin (ATR). Phytochemical profiles using chromatographic analysis were confirmed. The antioxidant activity was evaluated using in vitro chemical tests and in vitro enzymatic cells-free tests, namely superoxide dismutase (SOD), glutathione peroxidase (GPx), glu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 110 publications
(156 reference statements)
1
8
0
Order By: Relevance
“…The most recent literature affirms the legitimacy of integrating theoretical techniques with in vitro methods. The results of research conducted by Studzińska et al [ 75 , 80 ] confirmed that the theoretical models aimed at determining the activity of caperatic acid and atranorin in relation to AChE and BChE (cholinesterase enzymes) were consistent with the in vitro results. Promyos et al [ 4 ] indicate that molecular docking allows to correlate the differences in the structure of anthocyanins with their glucosidase-inhibiting effect.…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…The most recent literature affirms the legitimacy of integrating theoretical techniques with in vitro methods. The results of research conducted by Studzińska et al [ 75 , 80 ] confirmed that the theoretical models aimed at determining the activity of caperatic acid and atranorin in relation to AChE and BChE (cholinesterase enzymes) were consistent with the in vitro results. Promyos et al [ 4 ] indicate that molecular docking allows to correlate the differences in the structure of anthocyanins with their glucosidase-inhibiting effect.…”
Section: Resultssupporting
confidence: 70%
“…Molecular docking is a valuable technique used to confirm interactions between enzymes. The latest literature reports show that molecular docking is crucial for discovering new compounds for medical use, predicting interactions between ligands and targets, and comprehending the relationships between structure and activity [ 74 , 75 ]. In silico study of anthocyanidins and anthocyanins, activity has been of interest in various biomedical applications [ 4 , 76 , 77 , 78 , 79 ].…”
Section: Resultsmentioning
confidence: 99%
“…The extracts were stored at −20 • C until the next analysis. Total polyphenolic content (TPC) was determined using the procedure described by Studzi ńska-Sroka et al [43]. Briefly, a 96-well test plate was used for the study.…”
Section: Extract Preparationmentioning
confidence: 99%
“…A previously described DPPH analysis was used to determine the antiradical activity [43]. A total of 25.0 µL of the tested extract (3.125-0.391 mg dry plant material/mL) and 175.0 µL of DPPH solution (0.2 mM in methanol) were transferred to a 96-well plate.…”
Section: Dpph Analysismentioning
confidence: 99%
“…They confirmed that the effect of the extract against butyrylcholinesterase (BChE) is stronger than against AChE. In another study [ 48 ], both experimental and theoretical analyses verified that atranorin possesses a high capacity to inhibit AChE. Alhaithloul et al [ 49 ] utilized molecular docking to show that limonene (the main compound in the rosemary methanolic extract) forms stable complexes with DNA gyrase A.…”
Section: Introductionmentioning
confidence: 97%